2009
DOI: 10.4314/njps.v24i1.46380
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Gavage Treatment With Pulverised Garcinia Kola Seeds On Erythrocyte Membrane Integrity And Selected Haematological Indices In Male Albino Wistar Rats

Abstract: Summary: This study examines the effect of the whole seed of Garcinia kola (GKS) on various blood parameters, in adult male albino rats. Five groups, of 6 animals per group, were treated by gavage with suspensions of graded concentrations of GKS daily for 5 weeks. The animals were then sacrificed and blood was obtained for estimation of the data herein presented. Packed red cell volume (PCV), hemoglobin concentration (Hb), and red blood cell count (RBC) showed significantly (P < 0.05, Student's t-test) increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
4
4
3
3
Order By: Relevance
“…Osifo et al (2013) also showed significant reduction (P < 0.05) in the PCV, Hb, neutrophil and eosinophil counts of rabbits fed with methanolic extract of G. kola and significant increase (P <0.05) in the WBC and lymphocyte counts and an unchanged monocyte and basophil counts. The result therefore disagrees with Ahumibe and Braide (2009) who reported significant increase in PCV, Hb, and RBC in response to treatment with G. kola. Saponin content of G. kola may be responsible for these results.…”
Section: Effect Of G Kola Treatment On the Haematological Parameterscontrasting
confidence: 55%
See 2 more Smart Citations
“…Osifo et al (2013) also showed significant reduction (P < 0.05) in the PCV, Hb, neutrophil and eosinophil counts of rabbits fed with methanolic extract of G. kola and significant increase (P <0.05) in the WBC and lymphocyte counts and an unchanged monocyte and basophil counts. The result therefore disagrees with Ahumibe and Braide (2009) who reported significant increase in PCV, Hb, and RBC in response to treatment with G. kola. Saponin content of G. kola may be responsible for these results.…”
Section: Effect Of G Kola Treatment On the Haematological Parameterscontrasting
confidence: 55%
“…The numerical values of the gain in RBC are 1.30, 0.20, 0.15 and 0.15 × 10 6 /mm 3 . Ahumibe and Braide (2009) reported increase in RBC for Garcina treated rats. Esomonu et al (2005) who recorded increased RBC values in Wistar rats medicated with ethanol extract of G. kola seed.…”
Section: Effect Of G Kola Treatment On the Haematological Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, Garcinia kola treatment had no effect on haemoglobin (Hb), packed cell volume (PCV), red blood cell (RBC) count and its indices, including, mean cell volume (MCV), mean cell haemoglobin (MCH) and mean cell haemoglobin concentration (MCHC). This is in disagreement with the studies of Ahumibe and Braide 22 and Uko et al, 23 . Ahumibe and Braide 22 reported elevation of RBC, PCV and Hb after treatment with Garcinia kola, but at much higher doses (300 -1200 mg/kg).…”
Section: Resultscontrasting
confidence: 78%
“…Consequently, the cells in the body experience oxygen deficiency. Continuous damage on erythrocyte membrane can lead to anemia and reduce blood hematocrit levels (Ahumibe and Braide, 2009). In this study, the decline in hematocrit level after consuming the roselle capsules for 30 days was still within the normal range.…”
Section: The Effects Of Red Roselle Capsule On Hematocrit Thrombocytmentioning
confidence: 46%